Joan Littlewood - Holdsworth, Nadine (London : Routledge, 2006)
1. BIOGRAPHY IN POLITICAL, SOCIAL AND ARTISTIC CONTEXT -- Introduction -- Early Life -- Early Career: 'Theatre as a Weapon': Theatre of Action and Theatre Union (1935- 1945) -- On the Road: The Creative Ensemble (1945-1952) -- Popular Theatre/Critical Success (1953-1963) -- Community Initiatives (1963-1975) -- ## ##2. JOAN LITTLEWOOD'S WORKING METHOD -- Introduction -- What was Littlewood Against? -- Attitude to Acting -- Promoting the Creative Ensemble -- Approaches to Actor Training -- Creating a Movement Based Theatre: The Influence of Laban -- Using and adapting Stanislavsky -- Realising the World of the Play -- Improvisation: Creating the Conditions for Theatrical Invention -- Keeping a Show Alive -- Conclusion -- ## ##3. DESCRIPTION AND ANALYSIS OF OH WHAT A LOVELY WAR -- Introduction -- 1963: Political and Cultural Context -- The War Game -- Theatricality -- Developing the Show -- The Pierrot Show -- Documentary Material/The 'Technological Actor; -- The Songs -- Act One -- Act Two -- Selling Out -- Impact and Influence -- ## ##4. PRACTICAL EXERCISES -- Introduction -- Aims -- Approach -- Warm-Up Exercises -- The Performing Body in Space and Time -- Releasing the Imagination -- Working with Text -- Ensemble Playing -- Working with Documentary Sources --
Includes bibliographical references and index.
boek
Keywords: Littlewood, Joan. -- Criticism and interpretation